46.8k views
5 votes
13 + 11s = -15 + 8s − 20

1 Answer

5 votes

Answer,

S = -16

Explanation,

Step 1: Simplify both sides of the equation.

13 + 11s = − 15 + 8s − 20

13 + 11s = − 15 + 8s + − 20

11s + 13 = (8s) + (− 15 + − 20) (Combine Like Terms)

11s + 13 = 8s + − 35

11s + 13 = 8s − 35

Step 2: Subtract 8s from both sides.

11s + 13 − 8s = 8s − 35 − 8s

3s + 13 = − 35

Step 3: Subtract 13 from both sides.

3s + 13 − 13 = − 35 − 13

3s = − 48

Step 4: Divide both sides by 3.

3s/3 = −48/3

s = -16


Hope this helps :-)


User Maxim Borunov
by
6.0k points